Evaluation of Decentralized Website Performance Using Blockchain DNS - Putri, Bellia Dwi Cahya; Alim, Ilmam Fauzi Hashbil (Jurnal Teknologi dan Sistem Komputer, 2023)
Privacy violations and misuse of customer data are the failures of Web 2.0. Web 2.0 employs a centralized server that can be accessed by authorities. With the development of Web 3.0, which is built on blockchain and uses a decentralized application (dApp) to avoid privacy violations and data misuse. Decentralized systems can offer users privacy and autonomous control of the system, which is an important feature of consumer protection. Decentralized web development, also known as Web 3.0, was created using blockchain technology and the peer-to-peer network protocol (IPFS). In a decentralized website environment, data on the server can be linked to conventional domains (.com, .id, etc.) or to special domains provided by blockchain-based platform domains. Every transaction must be linked to the Ethereum wallet and cryptocurrency for the smart contract to function. This activity takes a long time and is a bad UX for decentralized web developers. To compare the performance of a decentralized web using blockchain DNS and a centralized web using conventional domains, a 15-minute usage scenario with a maximum of 50 users is used. The results show that the throughput and bandwidth of a decentralized web is higher than a centralized web.